GE_GERICHTE A/3200/2023 vom 22. Mai 2024 - GE Cour de justice (2024)
DÉCISION INCIDENTE;CHANGEMENT D'AFFECTATION;ZONE;VILLA;GÉRANT(SENS GÉNÉRAL);MAISON DE PROSTITUTION;DÉCISION D'IRRECEVABILITÉ | LPA.57.letc; LPA.4; LCI.1; LaLAT.19.al3; LProst.17.letd; LAT.22.al1; RCI.10B; LaLAT.19.al3